The Influence of Speed, Grease Type, and Temperature on Radial Contaminant Particle Migration in a Double Restriction Seal - Baart, P.; Green, T. M.; Li, J. X.; Lundström, T. S.; Westerberg, L. G.; Höglund, E.; Lugt, P. M. (Tribology transactions, 2011)
Microparticle image velocimetry (μPIV) is used to measure the grease velocity profile in small seal-like geometries and the radial migration of contaminant particles is predicted. In the first part, the influence of shaft speed, grease type, and temperatures on the flow of lubricating greases in a narrow double restriction sealing pocket is evaluated. Such geometries can be found in, for example, labyrinth-type seals. In a wide pocket the velocity profile is one-dimensional and the Herschel-Bulkley model is used. In a narrow pocket, it is shown by the experimental results that the side walls have a significant influence on the grease flow, implying that the grease velocity profile is two-dimensional. In this area, a single empirical grease parameter for the rheology is sufficient to describe the velocity profile. In the second part, the radial migration of contaminant particles through the grease is evaluated. Centrifugal forces acting on a solid spherical particle are calculated from the grease velocity profile. Consequently, particles migrate to a larger radius and finally settle when the grease viscosity becomes large due to the low shear rate. This behavior is important for the sealing function of the grease in the pocket and relubrication.